Photography Arts Centre: an architectural exploration of place and identity in Bloemfontein - Dzansi, Kodzus Daniel (University of the Free State, 2019)
This dissertation explores the transformation of a nonplace into a place by developing an identity in an architectural intervention with the aid of its context. It proposes a photography training centre in the central part of Bloemfontein rich in urban diversity. The aim of this photographic facility is to design a meaningful place of learning and activity by including and expanding upon the context’s urban fabric and making it a part of the site’s new identity. The client is an emerging small business by the name of DYD and Sons Pty Limited. This company believes that it could leverage on a collaborative effort between it and the Central University of Technology’s (CUT) Department of Design and Studio Art, Bloemfontein Camera Club and the College of Digital Photography to develop a non-linear model of learning the art of photography in the urban fabric of the centre of Bloemfontein. The dissertation is split into four main parts. The study first recognises the problems and aims associated with the project in terms of typology, topology, morphology and building tectonics. The second part communicates the theoretical, conceptual and precedent framework that informs the design’s development. The third part is the exploration of the design process leading up to the proposed design resolution. Part four concludes the dissertation with a reflection on the design’s successes and comments on the design process.
Dissertation (M.Arch. (Architecture))--University of the Free State, 2019
Keywords: Identity; Urban activation; Public life; Context; Transformation non-place to place